INTEGRATED APPROACH IN FORMING ECO-VALEOLOGICAL CULTURE OF FUTURE OFFICERS IN NATIONAL GUARD OF UKRAINE - Zub, Olena Vadymyvna; Dem’yanishyn, Volodymyr Mykolayovych (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2018)
Introduction. Eco-valeological culture is a new way of individual existence, the individual behavior of the new strategy among its existence, which determined by active interaction of the two consciousness` forms – environmental and valeological world. Scientific substantiation of future officer`s eco-valeological cultural formation in the process of his professional training defines a need of clarification in common methodological approaches during the planning and conducting research in this area. Considering that the eco-valeological culture as a specific type of personal culture is formed by the integration of environmental and valeological culture, one of the leading methodological approaches to the process of its formation precisely must be an integrated approach. Purpose. To substantiate the integrated approach to the formation of eco-valeological culture of the National Guard of Ukraine future officers in the process of studying environmental disciplines. Methods. An integrated approach is directly related to systemic approach. Integration (from the Latin. Integration - recruitment, recovery) – the process of development, combining disparate parts and elements. Integration processes take place both in the existing system (in this case, they raise the level of integrity and organization), and when a new system still has not connected elements. In the process of integration in the system increases the amount and intensity of relationships between elements. Integration is viewed as a process or result of the process. Integration is not only strengthening ties, but also change the source elements. If there is no such change, then there is no amplification of ties. It is replaced by only mechanical association. Integration process means new integrity growth, which has a common scientific system, appropriate mechanisms of interrelation and changes in the elements, functions object of study, which are caused by feedback system tools and new skills, which were formed. There are foundations of integrating knowledge: ontological (the unity of the world), gnoseological (the unity of the human mind and the laws of thought), methodological (availability of scientific methods of research), social (human integrity). The latter determines the need for epistemological and methodological support of knowledge integration. Integration radically changes the content and structure of modern scientific knowledge, intellectual and conceptual possibilities of individual sciences. It is the most important mean to achieve unity of knowledge in a meaningful, structured, logical-epistemological, scientific, organizational, linguistics, semantic, methodological and pedagogical aspects. Methodological issues of scientific knowledge integration, including science and humanitarian, dedicated works of I.A. Akchurin, B.M. Kedrov, E.S. Markarian, O.N. Sychyvytsya. Educational integration is considered as the highest form of unity of purpose, principles and content of education and teaching as the creation of consolidated units based on interrelation of academic disciplines. The integration of disciplines is not the process of summation. It is the process of their union. The basis of this is the process of interrelation, complementarity, mutual penetration methods, concepts, theories that make up these subjects. Implementation of the learning process of integrated disciplines provides an important quality of education. It is productivity. Results. The article discloses the essence of using an integrated approach in the process of eco-valeological culture of National Guard of Ukraine future officers. It is the formation of eco-valeological culture of the person. Eco-valeological culture as a specific type of personal culture is forming in the process of integration eco-valeological culture and one of the leading methodological approaches to the process of its formation must be precisely integrated approach. It allows to consider eco-valeological culture of future officer category as an integrated, holistic education, consisting of interrelated components: knowledge and skills, ecological eco-valeological activities skills. Conclusion. Using an integrated approach to ensure the integration of environmental issues with the content valeological environmental sciences tends to strengthen environmental and valeological relationships and provides the structural components of the future officers` eco-valeological culture.